SISTEM MONITORING ABSENSI SISWA DENGAN NOTIFIKASI WHATSAPP KE ORANG TUA MENGGUNAKAN TEKNOLOGI RFID - Ishak, Yulanda. S; Salmawaty Tansa; Rahmat Deddy R Dako; Syahrir Abdussamad; Ikhsan Hidayat; Ulfatun Nadifa (Universitas Bina Taruna Gorontalo, 2025)
This study aims to develop an attendance monitoring system using RFID with WhatsApp notifications. The RFID system utilizes radio waves for object identification and tracking, the system also utilizes fonts as a supporting application as api-whatsapp. Application testing is used in 2 ways, blackbox testing and UAT (User Acceptance Test). From the results of the design of the attendance system quality measurement application, it was successfully realized with blackbox testing. Blackbox testing is a test that ensures that the system that has been designed runs properly and correctly, while UAT (User Acceptance Test) testing is the final test to ensure that the software meets user needs. The test results at SMK Negeri 5 Gorontalo show that the attendance system using RFID can read and process data accurately. The system also operates consistently by sending notifications to parents after students scan their attendance.